Jobhunters and the Work-Shy: Permanent Unemployment and the Willingness to take up Work - Csoba, Judit (Szociológiai Szemle, 2024)
The mass media daily enable us to learn more and more about Hungary’s economic difficulties and about the effect these generate in employment. The number of statistics that highlight an increase in the number and rate of unemployed people is growing. Significant as these figures are, they reveal very little about the plight of the people behind them.In addition to published statistical figures, a growing number of articles and analytical studies have recently appeared (cf. Bánfalvy 1991, Nagy 1991, Fekete-Szabó - Sándor, 1991) .In spite of all this, we have hardly any information of the difficulties and ways in which unemployed people are trying to find jobs to support their families. We do not know what happens to them in the course of ever-increasing unemployment; nor do we know what sort of financial crisis and mental anguish they go through as they proceed along the path which seems less and less hopeful. Little do we know what happens to them after their benefit is withdrawn.It is especially timely to study the problems of everyday life, bread-and butter worries and people’s attempts to cope at a time when the unemployment rate is continuously rising. Experts say that the unemployment rate in the two counties which we have studied (13% in Hajdú-Bihar County and 21% in Szabolcs-Szatmár-Bereg County at the end of 1992) has not peaked yet. In addition to those who are registered as unemployed and receive benefits, the number of those who, after their unemployment benefit is withdrawn, are left behind by the system unable to find new employment is considerable.In the middle of 1992, within the framework of an OTKA research programme and aided by the Hungarian Credit Bank’s Foundation for Hungarian Science, we had an opportunity to have a closer look at the unemployed and to gain experience as to how subtle and versatile this stratum is, which is often characterised by a mere rate.